PEMBUATAN ALAT PENJEMUR KOPI - Wahyudhi Sutrisno; Nur Amiralmahdi; Benny Wibowo (Universitas Islam Indonesia, 2020)
Drying of coffee beans in Kemiri village is done in a natural way that dried coffee beans under the sun with a grounded sack, there are no coffee farmers who use the tool to dry the coffee beans. Although, drying the coffee beans using the dryer tool can accelerate the drying process and save the time, without the rainy season constrained and produce better quality. Drying is done with a coffee drying tool can make the coffee beans dry more evenly and perfectly. The coffee drying tool uses principles such as the Nako window, which can rotate 180o-360o. Using a coffee drying tool can adjust the position of the slope of the container in accordance with the direction of the coming sun so that the coffee beans can dry more evenly